Os quadrinhos e a internet: Aspectos e experiências híbridas - Thiago Flavio Mallet e Leite (2009)
This work studies the ways in which digital comics (also known as webcomics) present themselves inside the Internet, emphasizing the contributions brought to the comic's language by computer network technology: as the comics aggregate elements like sound,hypertext, animation and interactivity, they acquire features that are impossible inside their original medium the press , setting up new methods for their creation and new ways for appreciate them.Beginning from a historical approach of the comics, taking into account their commercial development and artistical/technical improvement since their beginning, in the 19th century, until their transition to computer networks, in the end of 20th century, the research, supported by examples, makes a classification of the webcomics in two categories(Heirs and Hybrids), as well as a detailed analysis of the features which the comics can have only inside digital media, drawing a panorama about their production, conducted by researchers, independent authors, groups of comic artists and even great enterprises.The text also discusses the construction of a Hybrid webcomic, as a way to demonstrate, in the Internet, the possibilities of this artistical manifestation under the vision and the experience of the author as a researcher and comic book artist, explaining the employed skills under Adobe Flash and the conceptual bases of the narrative.